Particularities of the negative streamer propagation in homogeneous and inhomogeneous electric fields. Computer simulation - Manuilenko, O.V.; Golota, V.I. (Вопросы атомной науки и техники, 2013)
The results of numerical simulations of negative streamer propagation in nitrogen in the plane - to - plane and the needle - to - plane geometries are presented. Computer simulations has been performed by finite element method, which allows to accurately describe the boundaries of complicated shape. It is shown that the propagation velocity of the negative streamer in a nonuniform electric field (the needle - to - plane geometry) is always greater than its velocity in a uniform field (the plane - to - plane geometry) at the same electrical potentials on the electrodes. It is shown that with decreasing curvature radius of the needle the streamer propagation velocity increases. The growth of the streamer speed, with decreasing of the needle curvature radius, is stopped when the needle curvature radius reaches a certain critical size. It is shown that in the region of the strong nonlinearity, when the dynamics of the streamer propagation is determined by the space charge, its velocity as a function of the longitudinal coordinate is independent of the needle curvature radius.